A Study of Magnetic Aggregation—Gravity Separation for Separation of Coarse Magnetite Ores. (1997) - Yu–Shu, Zhang; De–Zhang, Luo; Shuyi, Liu
Abstract : This paper describes experiments on separation of coarse magnetite ores using magnetic aggregation—gravity separation (MAGS) process for the first time. The results show that the MAGS technology can have a coarser separation size as well as a higher grade of the the magnetic product than the traditional low—intensity magnetic separation technology.